MARGINAL ADAPTATION OF TWO TYPES OF MONOLITHIC PRESSABLE CROWNS SUPPORTED BY DIFFERENT IMPLANT ABUTMENTS AFTER THERMO-MECHANICAL FATIGUE - Zainab R. El Sharkawy; Ayat G. Montaser; Suad M. Hassan; Asmaa Abdelgawad; Fatma M. Abdel-Rahman; Inas M. Mohamed; Ashraf Marawan El Azzazy (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Purpose: Poly-ether-ether-ketone (PEEK) is a sole polymer material that has recently been introduced to dentistry; marginal gap is increased significantly after thermomechanical fatigue (TF) as well as cement dissolution and, lastly failure of restoration. The current research aimed to evaluate the marginal adaptation of two kinds of monolithic pressable crowns supported by different implant abutments after thermo-mechanical fatigue. Materials: Blocks of epoxy resin were used to insert twenty – eight titanium dummy implants and allocated into 2 groups according to type of implant abutments (n=14): titanium implant abutments group (Ti) and ceramic-reinforced poly-ether-ether-ketone implant abutments group (PEEK). Every group was then subdivided into 2 subgroups (n = 7) in accordance with the kind of crowns: monolithic lithium disilicate "IPS e.max Press" crowns subgroup (EP) and monolithic ceramic reinforced poly-ether-ether-ketone (BioHPP Granulates) crowns subgroup (BG). All crowns were fabricated by means of the pressing technique. After surface treatments, adhesive cementation was performed for all crowns.  The samples were subjected to thermomechanical fatigue (TF). Marginal adaptation was measured before and after thermomechanical fatigue by means of a digital stereomicroscope.Results: PEEK group recorded lower marginal gap mean scores prior and following thermomechanical fatigue (29.06±7.84µm) (39.70±12.00µm) respectively compared to Ti group (41.57±8.82µm) (51.02±12.53µm) respectively. (EP) recorded lower marginal gap mean scores compared to (BG) prior and following thermomechanical fatigue in both different implant abutments.Conclusions: For all tested materials, the marginal gap mean scores documented in the current research were within the limits of standards that are deemed appropriate by clinicians.